PENERAPAN MAGANG KOGNITIF (COGNITIVE APPRENTICESHIP) UNTUK MENGAJARKAN KETERAMPILAN METAKOGNITIF DAN HASIL BELAJAR KOGNITIF SISWA - Rokhmah Wati, Dian Anisa; Tukiran, Tukiran; Ibrahim, Muslimin (JPPS (Jurnal Penelitian Pendidikan Sains), 2013)
The main aim of this research are to describe (1) cognitive learning outcomes of students who were taught using the cognitive apprenticeship using reciprocal teaching (RT), scardamalia and bereiter?s F.W (SB), and schoenfeld problem solving (SPS) strategies and (2) metacognitive skill level of students who are taught using the cognitive apprenticeship with RT, SB, and SPS strategies. This type of research is experimental research using the static group pretest-posttest design consisting of three classes of experiments with different treatments. Research subjects are students of XI IPA 2 SMA Darul Ulum Unggulan BPPT Jombang by the number of each class of experiments is 22 students. Instruments used are in the form of test and questionnaire. Students' cognitive learning outcomes data obtained will be analyzed with one way ANOVA using SPSS 19 and questionnaire data will be described.The result of data analysis revealed that Ho is rejected and Hi is accepted. It means that there was differences in cognitive learning outcomes of students who were taught using the cognitive apprenticeship with RT, SB, and SPS strategies. Metacognitive skill level of individual students experiencing increased tendency for RT, SB, and SPS class, while the average grade of students' metacognitive skills is in grade 3, developing grade for RT and SB class, while grade of students' metacognitive skills is in grade 4, ok grage for SPS class. It can be concluded that the cognitive apprenticeship learning with SPS strategy can be used to teach metacognitive skills with more scaffolding and advised to use RT and SB strategies for suitable characteristics topic (reading and writing)Tujuan utama penelitian ini adalah untuk mendeskripsikan (1) Hasil belajar kognitif siswa yang diajarkan menggunakan magang kognitif dengan strategi reciprocal teaching (RT), scardamalia and bereiter?s F.W (SB), dan schoenfeld problem solving (SPS), (2) Tingkat keterampilan metakognitif siswa yang diajarkan menggunakan magang kognitif dengan strategi RT, SB, dan SPS. Jenis penelitian yang dilakukan adalah experimental research menggunakan static group pretest- postest design yang terdiri dari tiga kelas eksperimen dengan perlakuan yang berbeda-beda. Subjek penelitian yaitu siswa kelas XI IPA SMA Darul Ulum 2 Unggulan BPPT Jombang dengan jumlah masing-masing kelas eksperimen adalah 22 siswa. Instrumen yang digunakan berupa soal tes dan angket. Data hasil belajar kognitif siswa yang diperoleh akan dianalisis dengan anava satu jalur menggunakan SPSS 19 dan data angket akan dideskripsikan. Hasil analisis data menunjukkan terdapat perbedaan hasil belajar kognitif siswa yang diajar menggunakan magang kognitif dengan strategi RT, SB, dan SPS. Tingkat keterampilan metakognitif siswa secara individual mengalami kecendrungan meningkat untuk kelas RT, SB, dan SPS, sedangkan secara rata - rata kelas tingkat keterampilan metakognitif siswa berada pada tingkat 3 yaitu tingkat developing untuk kelas RT, dan SB, sedangkan untuk kelas SPS berada pada tingkat 4 yaitu tingkat ok. Disimpulkan bahwa pembelajaran magang kognitif dengan strategi SPS dapat digunakan untuk mengajarkan keterampilan metakognitif, dengan pendampingan yang lebih maksimal dan disarankan untuk menerapkan strategi RT dan SB pada topik yang memiliki karakteristik yang sesuai yaitu membaca dan menulis